Habitus, maldade e permanência: o problema do mal e os limites do conhecimento sociológico - Pontes, Nicole Louise Macedo Teles de (2014)
The objective of this dissertation is to delineate the trajectory of a sociology of evil through a critique of the concept as it appears in philosophical works, the social psychology of Stanley Milgram and Phillip Zimbardo, and the sociological approaches of Zygmunt Bauman and Jeffrey Alexander. Thus, evil will be considered as a socially constructed object, which contains a generative capacity of symbolically classifying social reality and human actions through formative relations of subjects and communities. This rereading of evil as a sociological object is fundamentally based on the dispositional action theory of Pierre Bourdieu, especially in regards to its concepts of habitus and social libido. As such, evil as an empirical problem will be considered through an analysis of the photographs taken by American soldiers in 2003 at the Abu Ghraib military prison in Iraq.